1996
DOI: 10.1139/e96-072
|View full text |Cite
|
Sign up to set email alerts
|

40Ar/39Ar phlogopite and U – Pb perovskite dating of lamprophyre dykes from the eastern Lake Superior region: evidence for a 1.14 Ga magmatic precursor to Midcontinent Rift volcanism

Abstract: Thin lamprophyre dykes are abundant in the vicinity of the ca. 1.1 Ga Midcontinent Rift System and the late Archean – Early Proterozoic Kapuskasing Uplift in the Canadian Shield northeast of Lake Superior. However, the relationship between these dykes and spatially associated alkalic-carbonatite complexes has been unclear. To ascertain the temporal relationship between the two, we have determined, by 40Ar/39Ar and U–Pb dating, precise emplacement ages for six lamprophyre dykes from the region. The [Formula: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…The ~1144‐Ma ultramafic lamprophyre dikes (Queen et al, ) and the ~1142 Abitibi diabase dikes (Krogh et al, ) that crop‐out northeast of Lake Superior (Ontario, Canada; Figure ) represent the earliest magmatic events related to MCR (Table ). For both suites, local dike trends form a fan pattern radiating from a common center in the Lake Superior basin (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ~1144‐Ma ultramafic lamprophyre dikes (Queen et al, ) and the ~1142 Abitibi diabase dikes (Krogh et al, ) that crop‐out northeast of Lake Superior (Ontario, Canada; Figure ) represent the earliest magmatic events related to MCR (Table ). For both suites, local dike trends form a fan pattern radiating from a common center in the Lake Superior basin (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…For both suites, local dike trends form a fan pattern radiating from a common center in the Lake Superior basin (Figure ). Based on similar age and radiating dike trends, Queen et al () suggested that the lamprophyre and Abitibi dikes represented the incipient magmatic activity of the Midcontinent rifting, preceding the main rift magmatism by ~35 Ma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intruded by Proterozoic diabase dykes. The youngest igneous rocks of the Wawa area are carbonatites and lamprophyres with ages of 1000-1140 Ma (Gittins et al 1967;Sage 1996;Queen et al 1996;Sage and Crabtree 1997).…”
Section: Regional Geologymentioning
confidence: 99%
“…Despite their relatively small-volume, increasing significance is being attached to the studies on lamprophyres owing to their (i) role in understanding of the large-scale geodynamic processes such as continental extension (e.g., Larsen and Rex, 1992;Queen et al, 1996;Tappe et al, 2006), mantle plume-lithosphere interactions (e.g., Gibson et al, 2006;Orejana et al, 2008;Kerr et al, 2010), continental break-ups and collisions (e.g., Foley et al, 2002;O'Leary et al, 2009;Rocchi et al, 2009) and mantle-enrichment processes (e.g., Beard et al, 1996;Guo et al, 2004;Srivastava and Chalapathi Rao, 2007), (ii) entrapped lower-crustal and mantle xenoliths which serve as snapshots to the lower portions of the 1367-9120/$ -see front matter Ó 2011 Elsevier Ltd. All rights reserved. doi:10.1016/j.jseaes.2011.09.009…”
Section: Introductionmentioning
confidence: 99%